The impact of sodium-glucose cotransporter-2 inhibitors on the incidence, therapy, and outcomes of fournier gangrene: insights from a systematic review of case reports - Yufi Aulia Azmi; Firas F. Alkaff; Kevin Muliawan Soetanto; Soetojo Wirjopranoto; Maarten J. Postma; Abdul Khairul Rizki Purba (Systematic Reviews)
Abstract Background The clinical characteristics, therapy, and outcome of Fournier Gangrene (FG) in patients using sodium-glucose cotransporter-2 inhibitors (SGLT2i) were examined in this systematic review. Methods Without a publication year restriction, we searched PubMed, ScienceDirect, and Cochrane. Additionally, we manually searched bibliographies using the terms "Fournier's gangrene" and "SGLT2 inhibitors." The requirements for inclusion were the English language case reports with specific patient data and FG patients with diabetes who were using SGLT2 medication. The risk of bias was analyzed utilizing the Joanna Briggs Institute checklists. Results A total of 78 studies were identified, and 14 of them were included in this review. The duration of SGLT2i use varied from 6 months to 6 years. The patients’ age varied from 34 to 72 years, with 10 studies including male participants only and patients with obesity. All studies have discontinued SGLT2i and replaced them with other anti-diabetic drugs. Therapy options included perianal ring block, insulin, rigid sigmoidoscopy, aggressive debridement, antibiotics, fluid resuscitation, incision, drainage, surgery, hyperbaric oxygen therapy, plastic surgery, and fasciocutaneous flaps. Seven studies reported patients discharged in the range of 9–51 days. Conclusions The incidence of FG following SGLT2i use is rare. Therapy was performed by replacing SGLT2i with other anti-diabetic drugs. The patient's outcome improved after treatment.